Strategies for Successfully Completing Online Professional Development - Kim, Kyeong-Hwa; Morningstar, Mary E; Erickson, Amy Gaumer (International Journal of Knowledge Content Development & Technology, 2011)
Recently, increasing demand for teacher professional development and significant advances in information and communication technologies has led to a proliferation of online professional development. In spite of online professional development's popularity and advantages, research indicates that there is a concern of considerably high dropout rates of online learners. Therefore, to reduce the dropout rates of the learners, this paper is designed to help teachers identify professional development opportunities that are tailored to their needs as well as successfully complete these learning experiences. To achieve the purpose of the study, the paper explores the considerations for evaluating the characteristics of online learners and online professional development. Using these evaluations, this paper provides practical strategies for helping elementary and secondary education teachers successfully complete online professional development without dropping out an online course. URL: http://ijkcdt.net/xml/00640/00640.pdf